2016
DOI: 10.1515/revce-2015-0067
|View full text |Cite
|
Sign up to set email alerts
|

Marangoni effect in nonequilibrium multiphase system of material processing

Abstract: In a nonequilibrium multiphase system, the Marangoni effect has important influence on interphase heat and mass transfer induced by interfacial tension gradient associated with either solutal or thermal gradients in numerous applications. Although the basic knowledge of the Marangoni effect has made great progress, its mechanism is not yet fully recognized. An in-depth understanding of the basic principles of heat and mass transport induced by the Marangoni effect is important for better operation of interphas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 91 publications
0
14
0
Order By: Relevance
“…Experimental data on the stability threshold of Marangoni instabilities in drying polymer films are, however, scarce. Several authors have acknowledged this in the past [ 39 , 43 , 44 ]. In a recent comprehensive review on multiphase Marangoni convection, Wang et al explicitly stress the need for new quantitative experiments regarding convective instabilities in drying polymer films [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental data on the stability threshold of Marangoni instabilities in drying polymer films are, however, scarce. Several authors have acknowledged this in the past [ 39 , 43 , 44 ]. In a recent comprehensive review on multiphase Marangoni convection, Wang et al explicitly stress the need for new quantitative experiments regarding convective instabilities in drying polymer films [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have acknowledged this in the past [ 39 , 43 , 44 ]. In a recent comprehensive review on multiphase Marangoni convection, Wang et al explicitly stress the need for new quantitative experiments regarding convective instabilities in drying polymer films [ 44 ]. Bassou et al reported experimental findings of cellular convective instabilities in drying polystyrene-toluene films with an initial thickness of [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first one is the gradient force in the tilted front that could push the void out of the region of high intensity. The second is a thermocapillary force, which pushes the void into the region of high temperature and intensity (Marangoni effect) 53 . When the laser writing is in the direction against the tilt (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Amongst the earlier works upon convective instabilities, we can mention the theoretical contribution by Pearson [17] for surface tension driven ows (Bénard-Marangoni instabilities) and the experiments by Blair and Quinn [4] for the buoyancy-driven ows (Rayleigh-Bénard instabilities). A recent numerical, experimental and theoretical review involving surface tension instabilities has been published by Wang et al [22] to elucidate the mechanisms of the Marangoni eect.…”
Section: Introductionmentioning
confidence: 99%